Neurotensin receptor 1 signaling promotes pancreatic cancer progression. Issue 1 (20th November 2020) - Takahashi, Kei; Ehata, Shogo; Miyauchi, Kensuke; Morishita, Yasuyuki; Miyazawa, Keiji; Miyazono, Kohei
Abstract : Pancreatic cancer is one of the cancers with the poorest prognosis, with a 5‐year survival rate of approximately 5–10%. Thus, it is urgent to identify molecular targets for the treatment of pancreatic cancer. Using serial transplantations in a mouse pancreatic orthotopic inoculation model, we previously produced highly malignant pancreatic cancer sublines with increased tumor‐forming abilities in vivo . Here, we used these sublines to screen molecular targets for the treatment of pancreatic cancer. Among the genes with increased expression levels in the sublines, we focused on those encoding cell surface receptors that may be involved in the interactions between cancer cells and the tumor microenvironment. Based on our previous RNA‐sequence analysis, we found increased expression levels of neurotensin (NTS) receptor 1 (NTSR1) in highly malignant pancreatic cancer sublines. Furthermore, re‐analysis of clinical databases revealed that the expression level of NTSR1 was increased in advanced pancreatic cancer and that high NTSR1 levels were correlated with a poor prognosis. Overexpression of NTSR1 in human pancreatic cancer cells Panc‐1 and SUIT‐2 accelerated their tumorigenic and metastatic abilities in vivo . In addition, RNA‐sequence analysis showed that MAPK and NF‐κB signaling pathways were activated upon NTS stimulation in highly malignant cancer sublines and also revealed many new target genes for NTS in pancreatic cancer cells. NTS stimulation increased the expression of MMP‐9 and other pro‐inflammatory cytokines and chemokines in pancreatic cancer cells. Moreover, the treatment with SR48692, a selective NTSR1 antagonist, suppressed the activation of the MAPK and NF‐κB signaling pathways and induction of target genes in pancreatic cancer cells in vitro, while the administration of SR48692 attenuated the tumorigenicity of pancreatic cancer cells in vivo . These findings suggest that NTSR1 may be a prognostic marker and a molecular target for pancreatic cancer treatment. Abstract : Neurotensin (NTS) receptor 1 (NTSR1) is expressed in highly malignant pancreatic cancer cells, which were established by serial orthotopic transplantations. NTS/NTSR1 signaling contributes to the progression of pancreatic cancer through the activation of MAPK and NF‐κB signaling pathways and the induction of the genes related to inflammation. Targeting NTSR1 signaling by SR48692 inhibits pancreatic cancer progression.